2013
DOI: 10.1590/s0102-09352013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Potencial antiviral da quercetina sobre o parvovírus canino

Abstract: RESUMOAvaliou-se o efeito do flavonoide quercetina na replicação do parvovírus canino in vitro por meio do ensaio de determinação da atividade virucida (ensaio 1), ensaio de determinação da atividade sobre a célula (ensaio 2) e ensaio de tempo de adição das drogas em diferentes etapas do ciclo replicativo viral (ensaio 3). A quercetina apresentou significante atividade antiviral, com valores máximos de redução do título viral de 96,3% no ensaio 1, 90% no ensaio 2 e 90% no ensaio 3. Os efeitos mais expressivos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies show quercetin can bind with glycoproteins from the viral envelope and cellular receptors by modifying their chemical structure and blocking the virusbinding site. Brum et al [63] demonstrated a reduction in the virucide activities of some viruses with this substance, while Carvalho et al [64] confirmed its effects against canine parvovirus in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show quercetin can bind with glycoproteins from the viral envelope and cellular receptors by modifying their chemical structure and blocking the virusbinding site. Brum et al [63] demonstrated a reduction in the virucide activities of some viruses with this substance, while Carvalho et al [64] confirmed its effects against canine parvovirus in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…No Quadro 1, pode-se visualizar os principais constituintes já detectados na espécie supracitada. (CARVALHO et al, 2013;PEREIRA, 2017;SOUZA, 2009).…”
Section: Perfil Fitoquímico Da Fava D'antaunclassified
“…These negative results differ from those reported in previous studies with these plant species. Divergences may be related to several variables, such as (1) variations in the concentrations of secondary metabolites present in the plants, related to factors that may influence compound extractions (discussed above); (2) the chemical structure of these metabolites; (3) the fact that the phytochemical mechanism of action on the interaction capacity with the virus is different for each pathogen (Carvalho et al, 2013); and (4) the possibility of synergism or antagonism between extracted compounds (Cos et al, 2006;Kumar, Pandey, 2013). The aim of this study was not to investigate the constituents or their relationships that could be responsible for the observed effects, both in the cytotoxicity assays and in the antiviral activity trials.…”
Section: N T H I S S T U D Y T W O S P E C I E S B E L O N G I N Gmentioning
confidence: 99%